Software technologies : applications and foundations : STAF 2018 Collocated Workshops, Toulouse, France, June 25-29, 2018, Revised selected papers /: applications and foundations : STAF 2018 Collocated Workshops, Toulouse, France, June 25-29, 2018, Revised selected papers. ([2018]) - Unknown
No abstract available